A condição humana do paciente laringectomizado total: perspectivas para a clínica - Barbosa, Leopoldo Nelson Fernandes (2008)
The treatment of patients with larynx cancer who carry through the surgery of Total Laringectomy (TL), frequently implies the necessity of aggressive procedures that they can cause irretrievable esthetic and functional injuries, such as the use of nasogastric feeding, stoma, loss of speaks and the olfactive sense, difficulty to swallow certain foods and the impossibility of immersion in liquids, causing a series of repercussions a psychosocial dimension. Through a qualitative methodology based in the narrative of the patients and its caregivers, we objectify to investigate the possible psychosocial repercussions in the subjective construction of patients submitted to the TL. We search, also, to characterize the occured changes in the daily one of the patients, its familiar and social relations, with intention to understand as these changes affect its emotional balance and to understand its strategies of psychological confrontation. All the passage around the illness is lived by the patient and its family as a moment of crisis, crossed for a deep feeling of precariousness, demanding a series of readjustments that affect its routine expressivelly and of its family ones. Ahead of the diverse physical sequels decurrent of the TL and its treatment, the loss of speaks assumes with priority role taking the patient to isolate itself of its social conviviality, to move away from its professional functions, what it generates, consequently, improper feelings, low auto-esteem, shame and, even though, guilt for the belief of that its bad habits had contributed to become sick. The family, for its turn, suffers doubly: of a side for the perception of fragility and fear of loss and, of another one for attempts, nor always successful, to give support and to offer ambience for the new necessities that if present. One perceives, still, that on aspects to the religiosity, to the support of the family and trustworthiness in the team are faced as source of motivation for the treatment. The experience of become sick is extremely rich of is felt: dis-arming, easying to occupy with what it interests and reallyis present in here and now, asking for support spaces where abdicating of itself it implies in confiding for another one. Beyond going deep thematic relative to Clinical and Hospital Psychology, we believe that this research could assisting in them in the identification of clinical devices for the action of the Psychologist who works in this context. Other studies and reflections are necessary so that let us can more good understand these as much faces that involved the human being, without imprisoning it, considering it in its multiple singularity, however, can affirm that the contact with these patients and the search of understanding of its sufferings take us, each time more, to take the ethics of the care as the main referencial in our Clinical activity